The Costs of Irrigation Inefficiency in Tajikistan - World Bank (World Bank, Washington, DC, 2017)
The Aral Sea Basin consists of the drainage area of two major rivers, the Amu Darya and the Syr Darya. The rivers originate in the Tien Shan Mountains and the Pamirs, and run through Afghanistan, Kazakhstan, the Kyrgyz Republic, Tajikistan, Turkmenistan and Uzbekistan. An estimated 116 k